Used Approaches In Formulating Accounting Standards in Iraq & Their Develop Importance: filed Study (Journal of Accounting and Financial Studies ( JAFS ), 2009)
This research aims to show the most important approaches applicable in forming the accounting standards , the  importance approaches used to formulate local accounting standards & the  need to cancel or develop the unified accounting system in Iraq besides activate the local auditing & accounting standards council to issue accounting standards able to save the relevance & Reliable accounting information that serve the decisions of stockholders and others of stakeholders in the incorporate companies , especially the companies listed in the Iraq securities exchange , So this study based partially on analyzing the questionnaire form which has been designed to inquiry the specialists and experts opinion about the accounting standards importance and the need to activate the accounting course in Iraq as to be comply with the new environmental changes from another hand , In addition to determine the specific bodies responsibility in this field , Such as auditing & Accounting standards council as well as Iraqi securities exchange & the commission supervised on , the study has reached to several conclusions & conclusions .